The art of deception - Pearson, Ridley (London : Orion, 2003)
Seattle police department macho man John LaMoia and cop psychologist Daphne Matthews deal with a case too slippery to close. Lou Boldt, the supervising officer, is also entangled in a conundrum of his own. As both cases heat up, so does the sexual tension between Matthews and LaMoia leading them both into unknown emotional territory. A hair-raising chase through Seattle's Underground, a little-known network of hundred-year-old streets that were paved over by the city decades ago, brings the story to its climax.
Keywords: Detective English fiction; Mystery fiction